Analisis Pengaruh Indikator Makroekonomi Terhadap Indeks Harga Saham Syariah di Indonesia Tahun 2011-2020 - Anyta Nur Wulan (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
This study aims to analyze macroeconomic variables such as inflation, BI rate, exchange rate, Money Supply, World Gold Prices, Deposit Interest Rates, Sharia Deposit Yields, Industrial Production Index to the Sharia Stock Price Index. Where the Sharia Stock Price Index used is the Indonesian Sharia Stock Index (ISSI) and the Jakarta Islamic Index (JII). This study uses time series data or secondary data from May 2011 to February 2020. The analysis technique used in this study is ECM (Error Correction Model). The results showed that in the long run, the exchange rate and gold price had a negative effect on the ISSI and JUB had a positive effect on the ISSI. In the short term only the exchange rate variable has a negative effect on the ISSI. While the research results for JII show that in the long run Indonesian bank interest rates, exchange rates, and gold prices have a negative effect on JII. Meanwhile, the variable money supply and deposit interest rates have a positive effect on JII. In the short term, the influencing variables are the Indonesian bank interest rate, the exchange rate and the gold price have a negative effect on JII.